2021
DOI: 10.1108/itse-09-2020-0211
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of virtual classroom adoption in Jordan: the case of princess Sumaya university for technology

Abstract: Purpose The purpose of this study is to investigate the factors that affect students’ behavioral intentions to use virtual classrooms at Princess Sumaya University for Technology (PSUT) in Jordan. Design/methodology/approach A quantitative research approach was adopted, an online survey method was used and the data were collected among students at PSUT in Jordan. A total of 511 responses were usable for analysis. A structural equation modeling partial least squares technique was used to examine the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…In other words, the magnitude of PU in education refers to students' view of the learning advantages of technology that can increase their academic scores. Meanwhile, PEOU measures the level of user confidence that the technology is simple and does not require much effort to use the technology [13], [18], [20]. Abdullah and Toycan, who researched the adoption of elearning in Iraq, found that PU and PEOUE are the primary elements in the TAM model [16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the magnitude of PU in education refers to students' view of the learning advantages of technology that can increase their academic scores. Meanwhile, PEOU measures the level of user confidence that the technology is simple and does not require much effort to use the technology [13], [18], [20]. Abdullah and Toycan, who researched the adoption of elearning in Iraq, found that PU and PEOUE are the primary elements in the TAM model [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The technology used in learning has a fast response time, provider support, and a pleasing appearance. Previous research has proven that the quality of a platform greatly influences the intention to use a platform [13], [20], [26]. Therefore, the first hypothesis is: H 1 : CAQ has a positive impact on PU In improving student learning outcomes, the role of the instructor is significant.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the attitude toward using technology has been proven to be affected by perceived usefulness and perceived ease of use (PEOU). While perceived usefulness measures the individuals’ perceptions of using technology and how that improves their skills, PEOU measures the degree to which individuals believe that using technology does not need much mental effort (Alrousan et al , 2022). In general, the literature shows inconsistency in the findings regarding the use of e-learning as a main platform for learning and teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Alqurashi (2016) pinpoints that self-efficacy concerns students’ knowledge and necessary skills for using virtual classrooms, which falls under “internet and information-seeking self-efficacy.” Many previous studies found that self-efficacy is a positive and significant predictor of the PEOU of e-learning systems (Alqurashi, 2016; Budu et al , 2018; Chao et al , 2018; Sylvia and Abdurachman, 2018). Alrousan et al (2022) found that perceived self-efficacy is one of the seven factors that have an indirect effect on the behavioral intentions to use virtual classroom. Their data analysis demonstrated that perceived self-efficacy had a significant positive impact on Jordanian students’ PEOU virtual classroom.…”
Section: Introductionmentioning
confidence: 99%